2011
DOI: 10.1111/j.1365-2036.2010.04567.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: ghrelin agonist TZP-101 relieves gastroparesis associated with severe nausea and vomiting - randomised clinical study subset data

Abstract: SUMMARY BackgroundLimited therapeutic options exist for severe gastroparesis, where severe nausea and vomiting can lead to weight loss, dehydration and malnutrition due to inadequate caloric and fluid intake. TZP-101 (ulimorelin) is a ghrelin receptor agonist that accelerates gastric emptying and improves upper gastrointestinal symptoms in diabetic patients with gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 34 publications
(45 reference statements)
0
40
0
Order By: Relevance
“…In dia betic patients with severe gastroparesis, the intravenous ghrelin agonist TZP101 (ulimorelin) has been shown to reduce nausea, vomiting and overall symptoms com pared with placebo ( Figure 3). 124 Oral ghrelin agonists are being evaluated.…”
Section: Prokinetic Medicationsmentioning
confidence: 99%
“…In dia betic patients with severe gastroparesis, the intravenous ghrelin agonist TZP101 (ulimorelin) has been shown to reduce nausea, vomiting and overall symptoms com pared with placebo ( Figure 3). 124 Oral ghrelin agonists are being evaluated.…”
Section: Prokinetic Medicationsmentioning
confidence: 99%
“…Small studies have shown reduced overall post-meal symptom intensity, postprandial fullness, and symptom improvement after treatment with TZP-101 (80 μg/kg) for four days in six patients with severe gastroparesis, compared with six who received placebo. This improvement was sustained in the 30-day follow-up period (18,19). Higher doses were not as effective for symptom relief as the 80-μg/kg dose, possibly because ghrelin receptor agonists reduce gastric accommodation, which may induce upper gastrointestinal symptoms (20).…”
Section: Figurementioning
confidence: 80%
“…The ghrelin receptor agonist ulimorelin (TZP-101) was evaluated in patients with gastroparesis and was shown to enhance gastric emptying in these patients [76]. Similarly, TZP-102, another oral ghrelin receptor agonist, showed reduction in symptoms of gastroparesis and was well tolerated [77].…”
Section: Ghrelin Receptor Agonistsmentioning
confidence: 98%